1041 Early detection of biventricular mechanical dysfunction in PLN R14del mutation carriers. (17th January 2020) - Taha, K; Te Rijdt, W P; De Bruin-Bon, H A C M; Cramer, M J M; Asselbergs, F W; Bouma, B J; Van Den Berg, M P; Teske, A J
Abstract: Funding Acknowledgements: PLN Genetic Heart Disease Foundation Background: Carriers of the phospholamban (PLN) R14del founder mutation may develop an arrhythmogenic and/or dilated cardiomyopathy. Overt disease is preceded by a pre-symptomatic phase of variable length in which structural abnormalities seem to be absent. Purpose: We aimed to explore echocardiographic characteristics of PLN R14del mutation carriers, particularly in early disease stages. Methods: We included 120 PLN R14del mutation carriers and classified them to the pre-symptomatic stage (no symptoms and no structural disease, n = 60), the arrhythmic stage (arrhythmic symptoms and left ventricular ejection fraction (LVEF) ≥50%, n = 30) or the structural stage (LVEF <50%, n = 30). We included 60 healthy control subjects who were age- and gender matched with pre-symptomatic mutation carriers. All subjects underwent comprehensive echocardiographic analysis, including deformation imaging. Results: Values are provided in the abstract table. Patients in the structural stage had significantly impaired left/right ventricular (LV/RV) function and increased LV/RV size when compared to the other mutation carriers (p < 0.001). In the pre-symptomatic and arrhythmic stage, LV function and volumes did not differ significantly from controls by conventional measurements. However, LV global longitudinal strain (GLS) and LV mechanical dispersion (MD) were already significantly impaired in the pre-symptomatic and arrhythmic stage when compared to controls (p < 0.001). RV function by conventional measurements was lower in arrhythmic subjects than in controls (p = 0.016). A strong linear correlation was found between LV GLS and RV GLS (r = 0.8, p < 0.001). Conclusion: Echocardiographic deformation imaging reveals biventricular mechanical alterations in PLN R14del mutation carriers before arrhythmic symptoms and overt structural disease. Longitudinal studies are needed to determine the incremental prognostic value of these findings.